Connecting Space to Village: Servir Himalaya at Work for Bringing Earth Observation to Societal Benefits - Bajracharya, Birendra; Murthy, MSR (Journal on Geoinformatics, Nepal, 2017)
Earth observation plays an important role in understanding earth as a system by providing repetitive and consistent view throughout the globe for regular assessment and monitoring. There are a number of initiatives working globally to facilitate and promote the earth observation applications. SERVIR is one such global initiative evolved through partnership between USAID and NASA with an overarching goal to improve environmental management and resilience to climate change. SERVIR-Himalaya is being implemented by ICIMOD to provide integrated and innovative geospatial solutions for generation and dissemination of information and knowledge resources on mountain environments in the Hindu Kush Himalaya region. The SERVIR applications are focused on the broad thematic areas which are also subset of the societal benefit areas of Global Earth Observation (GEO), namely - agriculture and food security, ecosystems and sustainable landscapes, and disaster risk management. Some of its applications in Nepal include agriculture drought monitoring; land cover dynamics; biomass estimation at local and national scales; climate change vulnerability to forest ecosystems; multi-scale disaster risk assessment; and forest fire detection and monitoring. Access to these applications and data are facilitated through ICIMOD’s Mountain Geoportal and Regional Database System. Regional and national training and workshops, on-the-job training, internships and exchange programs and technical backstopping are key capacity building components to enhance the capacity of national institutions in the regional member countries. These efforts are also seen as receiving feedback on the science applications, identify additional needs, and increase synergy by exploring opportunities for collaboration. Nepalese Journal on Geoinformatics, Vol. 14, 2015, Page: 8-12